A study on assessment of postoperative complications among major abdominal surgeries using Clavien-Dindo classification - Rapaka, Rohit Reddy; Reddy M., Venkata (International Surgery Journal, 2020)
Background: Surgical team always tries to provide consistently low incidence of major complications for patient undergoing any operation. Clavien-Dindo (CD) classification is the simplest way of reporting all complications. The main aim of this study was to test the usefulness of Clavien-Dindo classification in patients undergoing the abdominal surgery. In this study Clavien-Dindo classification has been used for assessment of postsurgical complications after major abdominal surgery. Methods: A total of 50 patients admitted to surgical wards for major abdominal surgery were evaluated through history, co-morbid condition and thorough clinical examination based on inclusion and exclusion criteria along with necessary investigations. Post-operative complications and management were recorded, and then postsurgical complication was classified based on Clavien-Dindo classification and assessed. Results: Most of the patients who developed complications were in the age group of 40-50 years. Most of the patients (32%) belonged to grade 2 complications. Serum creatinine, blood urea and post-operative stay were found to have direct relation with Clavien-Dindo grade of complications. Conclusions: The Clavien-Dindo classification represents an objective and simple way of reporting all complications in patients undergoing major abdominal surgeries and comparing the various complications between different surgeries. However, a definite statement on the clinical value of this classification system is not yet possible due to the small case number in this study, but the promising results should encourage further evaluation in larger cohort with the goal to possibly establish its validity as a standard clinical practice.